Numerical investigation of turbulent mixed convection flow and heat transfer characteristics of 2 × 2 subchannels with spacer grids - Jianping Long; Bao‐Wen Yang; Ting Wu; Bin Zhang (Energy Science & Engineering, 2023)
Abstract In turbulent mixed convection conditions, flow and heat transfer can deteriorate under specific conditions, thus affecting the performance of the safety of the system, which could imperil the safety of the nuclear reactor. In this paper, by analyzing the velocity, temperature distributions, and other thermal‐hydraulic parameters, the steady‐state computational fluid dynamics approach with the SST k–ω turbulence model used in this study was verified. Then, flow and heat transfer characteristics in turbulent mixed convection inside 2 × 2 subchannels with and without spacer grids were investigated. The results showed that the velocity profiles were distorted and the heat transfer capacity was impaired due to the influence of buoyancy. The Nusselt number ratio (Nu/Nuf) between turbulent mixed convection and forced convection increased with the increase of Reynolds number (Re) until unity but decreased with the increases of Grashof number (Gr) and Buoyancy parameter (Bo*).